2017
DOI: 10.1111/jfbc.12455
|View full text |Cite
|
Sign up to set email alerts
|

Biological evaluation and quantitative analysis of antioxidant compounds in pulps of the Amazonian fruits bacuri (Platonia insignisMart.), ingá (Inga edulisMart.), and uchi (Sacoglottis uchiHuber) by UHPLC-ESI-MS/MS

Abstract: Biological evaluation and quantitative analysis of antioxidant compounds in pulps of the Amazonian fruits bacuri (Platonia insignis Mart.), ing a (Inga edulis Mart.), and uchi (Sacoglottis uchi Huber) by UHPLC-ESI-MS/MS lg/mL), whereas uchi and its main metabolite bergenin displayed moderate antimicrobial activities.The results shed light into the potentials of Amazonian fruit sources. Practical applicationsPlant phenolics are essential components of functional foods, due to their antioxidant and enzyme inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
0
9
0
4
Order By: Relevance
“…Compounds with anti-microbial and anti-inflammatory potentials have been reported in bacuri pulp, which may explain these anti-infective effects observed for unfermented juice [ 47 , 48 ]. Similarly, some strains of L. rhamnosus exhibited inhibitory activity against E. coli infection [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compounds with anti-microbial and anti-inflammatory potentials have been reported in bacuri pulp, which may explain these anti-infective effects observed for unfermented juice [ 47 , 48 ]. Similarly, some strains of L. rhamnosus exhibited inhibitory activity against E. coli infection [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The highest antioxidant capacity was presented in UE samples (1602.7 ± 30.16 µmol Trolox g −1 ). Freitas et al [30] analyses fresh pulp of uxi and found 51.6 mg TE/100 g for ABTS. In general, the ethanolic extracts of fruits showed the higher antioxidant capacity for this methodology.…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
“…2). All of them focused on timber and food uses (Clement, Cristo-Araújo, Eeckenbrugge, Pereira, & Picanço-Rodrigues, 2010;Lopes, Crepaldi, & Lobão, 2017;de Freitas et al, 2018).…”
Section: Literature Reviewedmentioning
confidence: 99%
“…Besides that, some studies emphasize the dispersers preference for I. edulis than other tree species in the same environment (Lindell et al, 2013). In addition, it shows antioxidant activities with moderate biological activities (Souza et al, 2007;De Freitas et al, 2018).…”
Section: Literature Reviewedmentioning
confidence: 99%